PEACEFUL AND HUMANISTIC RESOLUTION OF DOMESTIC VIOLENCE CASES (RESTORATIVE JUSTICE AND CRIMINAL APPROACHES) - Ependi, Ependi; Umam, Shofiul; Luqman, Luby (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The implementation of restorative justice in solving domestic violence cases from a criminal law perspective has several continuities . The restorative justice approach prioritizes recovery and reconciliation, involves the active participation of all parties involved, and can prevent cycles of violence from recurring. However, it is important to consider that restorative justice is not always suitable for all cases of domestic violence and punishment which is classified as a serious violation and must be applied with caution. This paper will cover a statutory review (statute approach) regarding the prevention of domestic violence using a formal juridical perspective that applies in Indonesia. It will also discuss from the point of view of victims, perpetrators, and law enforcement officials regarding the restorative justice system and the legal relationship between the concept of preventing acts of violence, from within the applicable criminal law whether it is sufficient to protect victims when using a restorative justice system. This study will analyze the prevention of domestic violence with a restorative justice approach, the pattern of relationships between the victims and the perpetrators. The ultimate goal of this research is to see the application of restorative justice from criminal law and to determine the most effective restorative justice method in a peaceful and humane way. Using a normative method with a descriptive approach, then the method used for drawing conclusions from normative research, using a deductive method.